2021
DOI: 10.1021/acs.nanolett.1c04007
|View full text |Cite
|
Sign up to set email alerts
|

Charged Tubular Supramolecule Boosting Multivalent Interactions for the Drastic Suppression of Aβ Fibrillation

Abstract: Anti-Aβ therapy has dominated clinical trials for the prevention and treatment of Alzheimer’s disease (AD). However, suppressing Aβ aggregation and disintegrating mature fibrils simultaneously remains a great challenge. In this work, we developed a new strategy using a charged tubular supramolecule (CTS) with pillar[5]­arene as the backbone and modifying amino and carboxyl groups at the tubular terminals (noted as CTS-A, CTS-A/C, and CTS-C, respectively) to suppress Aβ fibrillation for the first time. Accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In this respect, most of the conventional bulk measurement‐based analytical methods, namely, the analog signal readout assays, are not quite satisfactory. In the past decade, with the rapid development of fluorescence imaging/counting technologies, [ 5‐8 ] a collection of elegant digital bioassays that can detect biomarkers at the single‐molecule level have opened a new way towards the quantification of trace amount of biomarkers. [ 9‐13 ] Totally different from the traditional analytical methods, in a typical digital bioassay, the low abundance of target molecules is isolated into numerous sealed microreactors, ensuring that at most one single target molecule is located in one microreactor.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…In this respect, most of the conventional bulk measurement‐based analytical methods, namely, the analog signal readout assays, are not quite satisfactory. In the past decade, with the rapid development of fluorescence imaging/counting technologies, [ 5‐8 ] a collection of elegant digital bioassays that can detect biomarkers at the single‐molecule level have opened a new way towards the quantification of trace amount of biomarkers. [ 9‐13 ] Totally different from the traditional analytical methods, in a typical digital bioassay, the low abundance of target molecules is isolated into numerous sealed microreactors, ensuring that at most one single target molecule is located in one microreactor.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…12,13 The recent focus in scientific research has been on the development of functional compounds that possess the ability to visualize Aβ40 aggregates at the nanoscale level and potentially influence the assembly of Aβ. 14,15 The recent compounds demonstrate fluorescence activation upon binding with Aβ aggregates, facilitating the targeted imaging and photo-oxygenation of these aggregates. Consequently, this process results in the reduction of Aβ aggregates, promoting their elimination via the microglial lysosomal route and subsequently reducing their neurotoxic effects.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, the amyloid cascade hypothesis dominated AD research, revealing that the main reason behind the disease is the accumulation of amyloid-β peptides produced by sequential cleavage of the amyloid precursor protein (APP). Despite intense research, the exact reason for AD remains unclear to researchers, thereby demanding radical approaches to obtain a cure for AD . Aβ40 is one of the most abundant Aβ species widely known as a trigger molecule for AD. Therapies targeting amyloid β have been the focus for almost 30 years. , The recent focus in scientific research has been on the development of functional compounds that possess the ability to visualize Aβ40 aggregates at the nanoscale level and potentially influence the assembly of Aβ. , The recent compounds demonstrate fluorescence activation upon binding with Aβ aggregates, facilitating the targeted imaging and photooxygenation of these aggregates. Consequently, this process results in the reduction of Aβ aggregates, promoting their elimination via the microglial lysosomal route and subsequently reducing their neurotoxic effects. , However, up-and-coming drugs recently failed to show clinical benefits in phase III trials .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, previous studies have demonstrated that Aβ peptides are negatively charged under physiological conditions and can interact with aromatic rings through π−π and hydrophobic interactions. 25,26 Thus, quinolinium derivatives are employed as the skeleton, and electron-rich aniline derivatives are used as the substituents to design spontaneous blinking fluorophores with Aβ aggregates targeting capability (Figure 1). From the experimental results, these probes exhibit good selectivity toward the β-sheet structure and can emit enhanced deep-red fluorescence after binding with Aβ aggregates.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Quinolinium derivatives bearing quaternary ammonium salts are redox-active compounds with good electron-accepting ability, which emerge as promising scaffolds for the formation of stable radicals. , Electron-donating groups such as phenyl substituents can stabilize the pyridyl radical by increasing the level of mixing of π* and σ* orbitals. Moreover, previous studies have demonstrated that Aβ peptides are negatively charged under physiological conditions and can interact with aromatic rings through π–π and hydrophobic interactions. , Thus, quinolinium derivatives are employed as the skeleton, and electron-rich aniline derivatives are used as the substituents to design spontaneous blinking fluorophores with Aβ aggregates targeting capability (Figure ). From the experimental results, these probes exhibit good selectivity toward the β-sheet structure and can emit enhanced deep-red fluorescence after binding with Aβ aggregates.…”
Section: Introductionmentioning
confidence: 99%